Polysulfates Block SARS‐CoV‐2 Uptake through Electrostatic Interactions. Issue 29 (9th June 2021) - Nie, Chuanxiong; Pouyan, Paria; Lauster, Daniel; Trimpert, Jakob; Kerkhoff, Yannic; Szekeres, Gergo Peter; Wallert, Matthias; Block, Stephan; Sahoo, Anil Kumar; Dernedde, Jens; Pagel, Kevin; Kaufer, Benedikt B.; et al.
Abstract: Here we report that negatively charged polysulfates can bind to the spike protein of SARS‐CoV‐2 via electrostatic interactions. Using a plaque reduction assay, we compare inhibition of SARS‐CoV‐2 by heparin, pentosan sulfate, linear polyglycerol sulfate (LPGS) and hyperbranched polyglycerol sulfate (HPGS). Highly sulfated LPGS is the optimal inhibitor, with an IC50 of 67 μg mL −1 (approx. 1.6 μm ). This synthetic polysulfate exhibits more than 60‐fold higher virus inhibitory activity than heparin (IC50 : 4084 μg mL −1 ), along with much lower anticoagulant activity. Furthermore, in molecular dynamics simulations, we verified that LPGS can bind more strongly to the spike protein than heparin, and that LPGS can interact even more with the spike protein of the new N501Y and E484K variants. Our study demonstrates that the entry of SARS‐CoV‐2 into host cells can be blocked via electrostatic interactions, therefore LPGS can serve as a blueprint for the design of novel viral inhibitors of SARS‐CoV‐2. Abstract : Negatively charged polysulfates can bind to the positively charged patches of RBD of SARS‐CoV‐2 and block viral interaction with host cells for infection inhibition. The synthetic linear polyglycerol sulfate (LPGS) exhibits higher virus inhibitory activity than heparin, but lower anticoagulant activity. Therefore, it is considered to be a promising substitute for heparin in clinical applications.